2021
DOI: 10.1007/s42064-021-0109-x
|View full text |Cite
|
Sign up to set email alerts
|

Metamodel-based multidisciplinary design optimization methods for aerospace system

Abstract: The design of complex aerospace systems is a multidisciplinary design optimization (MDO) problem involving the interaction of multiple disciplines. However, because of the necessity of evaluating expensive black-box simulations, the enormous computational cost of solving MDO problems in aerospace systems has also become a problem in practice. To resolve this, metamodel-based design optimization techniques have been applied to MDO. With these methods, system models can be rapidly predicted using approximate met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 172 publications
0
9
0
Order By: Relevance
“…On the other hand, researchers prefer the metamodeling method to avoid this situation. The surrogate metamodeling approach is commonly utilized in different engineering cases 37,38 . Commonly used metamodeling methods in CFD studies are RBF, KGA, and ANN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, researchers prefer the metamodeling method to avoid this situation. The surrogate metamodeling approach is commonly utilized in different engineering cases 37,38 . Commonly used metamodeling methods in CFD studies are RBF, KGA, and ANN.…”
Section: Resultsmentioning
confidence: 99%
“…The surrogate metamodeling approach is commonly utilized in different engineering cases. 37,38 Commonly used metamodeling methods in CFD studies are RBF, KGA, and ANN. ANN can be used instead of surrogate modeling as an artificial intelligence-based approximation technique to reduce the computational cost and enhance optimization efficiency and the approximation accuracy for modeling complex systems with computational difficulties.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…However, research on the PCC algorithm provided a large amount of information for subsequent analyses. Further, Google proposed an innovative congestion control scheme in 2016 named the dubbed BBR (Bottleneck Bandwidth and Round-trip propagation time) [ 21 , 22 ]. Certain concepts in the BBR are consistent with the PCC algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Certain concepts in the BBR are consistent with the PCC algorithm. Nonetheless, in [ 21 , 22 ], it was demonstrated that the BBR algorithm performed excellently in environments with a high bandwidth, long delay, and high packet loss rate.…”
Section: Methodsmentioning
confidence: 99%
“…As a powerful methodology to solve the complicated design problems of coupled engineering systems, multidisciplinary design optimization (MDO) has received extensive attention from industry and academia (Zhu et al, 2021a, b;Wang et al, 2018a, b;Zadeh et al, 2019;Meng et al, 2018Meng et al, , 2021aHe et al, 2020;Zhang et al, 2016;D ıaz et al, 2017;Xiao et al, 2015;Martins and Lambe, 2013). Following its success in aeronautics and astronautics engineering, the application field of MDO has been widely extended to other engineering fields, such as vehicles and ships (Wang et al, 2014;Jaeger et al, 2013;Balesdent et al, 2012;Miao et al, 2020a, b;Wu et al, 2017;Wang et al, 2017;Meng et al, 2021b;Yin et al, 2020;Shi et al, 2021;Li et al, 2021a, b). In MDO, design variables and parameters are often treated as deterministic input information.…”
Section: Introductionmentioning
confidence: 99%